Imatinib and Dasatinib Provoke Mitochondrial Dysfunction Leading to Oxidative Stress in C2C12 Myotubes and Human RD Cells - Bouitbir, Jamal; Panajatovic, Miljenko Valentin; Frechard, Theo; Roos, Noëmi Johanna; Krähenbühl, Stephan (Frontiers in Pharmacology, 2020)
Tyrosine kinases inhibitors (TKIs) can cause skeletal muscle toxicity in patients, but the underlying mechanisms are mostly unclear. The goal of the current study was to better characterize the role of mitochondria in TKI-associated myotoxicity. We exposed C2C12 murine myoblasts and myotubes as well as human rhabdomyosarcoma cells (RD cells) for 24 h to imatinib (1-100 µM), erlotinib (1-20 µM), and dasatinib (0.001-100 µM). In C2C12 myoblasts, imatinib was membrane toxic at 50 µM and depleted the cellular ATP pool at 20 µM. In C2C12 myotubes exposed to imatinib, ATP depletion started at 50 µM whereas membrane toxicity was not detectable. In myoblasts and myotubes exposed to dasatinib, membrane toxicity started at 0.5 µM and 2 µM, respectively, and the ATP drop was visible at 0.1 µM and 0.2 µM, respectively. When RD cells were exposed to imatinib, ATP depletion started at 20 µM whereas membrane toxicity was not detectable. Dasatinib was membrane toxic at 20 µM and depleted the cellular ATP pool already at 0.5 µM. Erlotinib was not toxic in both cell models. Imatinib (20 µM) and dasatinib (1 µM) reduced complex I activity in both cell models. Moreover, the mitochondrial membrane potential (Δψm) was dissipated for both TKIs in myotubes. In RD cells, the Δψm was reduced only by dasatinib. Both TKIs increased mitochondrial superoxide accumulation and decreased the mitochondrial copy number in both cell lines. In consequence, they increased protein expression of superoxide dismutase (SOD) 2 and thioredoxin 2, and cleavage of caspase 3, indicating apoptosis in C2C12 myotubes. Moreover, in both cell models, the mRNA expression of Sod1 and Sod2 increased when RD cells were exposed to dasatinib. Furthermore, dasatinib increased the mRNA expression of atrogin 1 and murf 1, which are important transcription factors involved in muscle atrophy. The mRNA expression of atrogin 1 increased also in RD cells exposed to imatinib. In conclusion, imatinib and dasatinib are mitochondrial toxicants in mouse C2C12 myotubes and human RD cells. Mitochondrial superoxide accumulation induced by these two TKIs is due to the inhibition of complex I and is probably related to impaired mitochondrial and myocyte proliferation.